PENGARUH PENGUMUMAN PERUBAHAN DIVIDEN TERHADAP ABNORMAL RETURN SAHAM DI BURSA EFEK INDONESIA - Evan, Nur; Sutanto, Aftoni (Universitas Ahmad Dahlan, 2012)
The information about increase and decrease of the cash dividend that it's be dividend by the company is one of information that be considered important enough for investor, because in the information include. The loading information that due to advantage prospect that will get by the company in the next time. It's caused a condition where the investors is met to the high uncertainty of the result of it's investment activity so it's increase and decrease information a cash dividend can be assumed as an indicator for repairing the advantage prospect company in the next time. This research examines information content of cash dividends announcements increase and decrease and the difference of average abnormal return between companies announcing of cash dividend. The result shows that those companies announcing the increase of cash dividends, the is reactive, especially in the t+6 after dividends announcement. It indicate that there is content information on the announcement of cash dividends increase. Mean while those companies announcing the decrease of cash dividends, the market is reactive, especially in the t+9 after announcement of cash dividends. The test of the difference of average abnormal return before and after on the announcement of the increase and the decrease of cash dividends, show that there is no difference between average abnormal return before and after announcement of increase and decrease cash dividends.